Connecting income distribution to market power and debt default with different degrees of inputs substitutability - Souza, Tiago Carvalho Machado de (2016)
This dissertation is composed of two articles in applied economics. The first intends to develop a better understanding of how economies’ income distribution relates to pricing decisions of firms with market power. The goal is to identify variables that induce companies’ price changes looking to the demand side — instead of the more usual supply side explanations. It is an intuitive framework that allows bringing together otherwise con-flicting results of the empirical literature. The economy’s per-capita income, income share of buyers and companies’ market size (share of population that purchases their goods) are factors that determine their pricing behavior and help explaining patterns observed in reality. The second article is about countries’ decision to not repay their public debt. The focus, however, is on the relative scarcity of productive inputs that results from defaulting, and how easy it is to substitute among them. It is a different way of looking at the economic costs generated when governments miss to pay their debts. The environment built provides interesting results, as for example interest rate spreads that emerge by just changing inputs’ elasticity of substitution, without relying on differences in agents’ risk aversion.